(untitled) (Research, Society and Development, 2024)
The production of foods without added sugar follows a growing global trend of dietary products, suitable for people who want healthier eating habits, to lose or control weight and for those with eating disorders, such as diabetics. Associated with this market perspective, the production of pasty dulce de leche with whey has grown a lot in the market due to the fact that whey is an abundant by-product of the cheese industry that has nutritional value. In view of this, the present research aimed to develop pasty dulce de leche without added sugar by replacing part of the milk with whey (25%, 35% and 50% whey) as well as preparing the briefing on the new product to be developed. The sweet formulations were subjected to physical, chemical, microbiological, sensory analysis and process performance. The formulation with the best sensorial acceptance was analyzed for a period of four months of storage (physical, chemical and microbiological analyses). A nutritional information table was also developed. The formulation that presented a higher acceptance rate for the sensorial attributes evaluated as well as a greater purchase intention was the formulation with 50% milk and 50% whey. The product remained microbiologically stable during storage. Pasty dulce de leche processed with milk and whey without added sugar proved to be an excellent alternative dairy product, providing yet another alternative to the growing market of innovative options in the food sector.